1998
DOI: 10.1128/jcm.36.9.2428-2433.1998
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Candida dubliniensis by Indirect Immunofluorescence Based on Differential Localization of Antigens on C. dubliniensis Blastospores and Candida albicans Germ Tubes

Abstract: There is a clear need for the development of a rapid and reliable test for the identification of Candida dubliniensis and for the discrimination of this species from Candida albicans. In the present study we have investigated the potential use of C. dubliniensis-specific antigens as a basis for its identification. We produced an anti-C. dubliniensis serum which, after adsorption with C. albicans blastospores, was found to differentially label C. dubliniensis isolates in an indirect immunofluorescence test. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 26 publications
(40 reference statements)
0
25
0
2
Order By: Relevance
“…The isolates, including 12 C. albicans from 11 patients and six C. dubliniensis from four patients, were identified by conventional mycological identification methods and by their carbohydrate assimilation patterns on ID 32C strips (bioMérieux, Marcyl'Etoile, France). C. dubliniensis isolates identities were confirmed by immunofluorescence as previously described [11,12]. Polymerase chain reactions were performed according to the method described by Alonso et al [13], using the primer AB1-12 (5 0 -CCTTGACGCA-3 0 ) purchased from Advanced Technologies Ltd. (Leatherhead, Surrey, UK).…”
Section: Rapd Of Candida Isolatesmentioning
confidence: 99%
“…The isolates, including 12 C. albicans from 11 patients and six C. dubliniensis from four patients, were identified by conventional mycological identification methods and by their carbohydrate assimilation patterns on ID 32C strips (bioMérieux, Marcyl'Etoile, France). C. dubliniensis isolates identities were confirmed by immunofluorescence as previously described [11,12]. Polymerase chain reactions were performed according to the method described by Alonso et al [13], using the primer AB1-12 (5 0 -CCTTGACGCA-3 0 ) purchased from Advanced Technologies Ltd. (Leatherhead, Surrey, UK).…”
Section: Rapd Of Candida Isolatesmentioning
confidence: 99%
“…Definitive identification of C. dubliniensis was done by means of their colony color and morphology in medium, 34 analysis by multiplex polymerase chain reaction, 35 and reactivity with a latex agglutination test specific for C. dubliniensis 36, † † and an anti-C. dubliniensis antiserum. 37 Statistical Analyses Descriptive analyses of data were expressed as mean -SD. Significance of group comparisons was determined by the Student t test or the chi-square test with the Yates' correction when appropriate.…”
Section: Specimen Collectionmentioning
confidence: 99%
“…Bikandi et al [50] demonstrated the possibility of using differences between C. albicans and C. dubliniensis cell wall localised antigens to differentiate between these species. Cross reactivity was, however, observed for C. krusei.…”
Section: Serological Characteristicsmentioning
confidence: 99%